Elk-3 is a KLF4-regulated gene that modulates the phagocytosis of bacteria by macrophages. Issue 1 (28th October 2014) - Tsoyi, Konstantin; Geldart, Adriana M; Christou, Helen; Liu, Xiaoli; Chung, Su Wol; Perrella, Mark A
Abstract : Down-regulation of Elk-3 by bacterial LPS, in part through the transcriptional repressor KLF4, allows for up-regulation of HO-1 and a compensatory phagocytic response in macrophages. Abstract: ETS family proteins play a role in immune responses. A unique member of this family, Elk-3, is a transcriptional repressor that regulates the expression of HO-1. Elk-3 is very sensitive to the effects of inflammatory mediators and is down-regulated by bacterial endotoxin (LPS). In the present study, exposure of mouse macrophages to Escherichia coli LPS resulted in decreased, full-length, and splice-variant isoforms of Elk-3. We isolated the Elk-3 promoter and demonstrated that LPS also decreased promoter activity. The Elk-3 promoter contains GC-rich regions that are putative binding sites for zinc-finger transcription factors, such as Sp1 and KLFs. Mutation of the GC-rich region from bp –613 to –603 blunted LPS-induced down-regulation of the Elk-3 promoter. Similar to the LPS response, coexpression of KLF4 led to repression of Elk-3 promoter activity, whereas coexpression of Sp1 increased activity. ChIP assays revealed that KLF4 binding to the Elk-3 promoter was increased by LPS exposure, and Sp1 binding was decreased. Thus, down-regulation of Elk-3 by bacterial LPS is regulated, in part, by the transcriptional repressor KLF4. Overexpression of Elk-3, in the presence of E. coli bacteria, resulted in decreased macrophage phagocytosis. To determine whether limited expression of HO-1 may contribute to this response, we exposed HO-1-deficient bone marrow-derived macrophages to E. coli and found a comparable reduction in bacterial phagocytosis. These data suggest that down-regulation of Elk-3 and the subsequent induction of HO-1 are important for macrophage function during the inflammatory response to infection.